1992
DOI: 10.1111/j.1096-3642.1992.tb00927.x
|View full text |Cite
|
Sign up to set email alerts
|

A unique sound production mechanism in the pipid anuran Xenopus borealis

Abstract: The totally aquatic pipid frog Xenopus borealis produces long trains of click‐like sound at high sound pressure levels (> 105 dB SPL) underwater at night. While X. borealis retains an essentially terrestrial respiratory tract, the larynx is highly modified in two ways. First, the cricoid cartilage is greatly expanded posteriorly to form a large ‘box’. Portions of this cricoid box are composed of an unusual elastic cartilage. Second, portions of the arytenoid cartilages are elaborated into calcified rods with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
81
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 17 publications
4
81
2
Order By: Relevance
“…Extensive neuroanatomical studies by Kelley and colleagues (Wetzel et al, 1985;Zornik and Kelley, 2007) identified a central calling circuit for the fully aquatic frog Xenopus laevis that does not depend upon respiration for calling (Yager, 1992). The Xenopus map closely matches the neurophysiological one for Lithobates depicted by Schmidt (1992).…”
Section: Fictive Vocalizations Predict the Temporal Patterns Of Sociamentioning
confidence: 62%
“…Extensive neuroanatomical studies by Kelley and colleagues (Wetzel et al, 1985;Zornik and Kelley, 2007) identified a central calling circuit for the fully aquatic frog Xenopus laevis that does not depend upon respiration for calling (Yager, 1992). The Xenopus map closely matches the neurophysiological one for Lithobates depicted by Schmidt (1992).…”
Section: Fictive Vocalizations Predict the Temporal Patterns Of Sociamentioning
confidence: 62%
“…The phylogenetic relationships of extant species have been described using both mitochondrial and nuclear deoxyribonucleic acid (DNA; Evans et al 2004). All species produce calls via contraction of the laryngeal muscles to pull apart a pair of cartilaginous disks, thus producing a "click" (Yager 1992); the temporal patterns of trains of clicks (trills) and click rates are unique to each species. While the mechanism of sound production is highly conserved, the rates at which these clicks are produced and thus the rate at which laryngeal muscles contract vary considerably among species, from two clicks per second in X. borealis (Yager 1992) to 70 in X. laevis (Kelley 2002).…”
Section: Introductionmentioning
confidence: 99%
“…All species produce calls via contraction of the laryngeal muscles to pull apart a pair of cartilaginous disks, thus producing a "click" (Yager 1992); the temporal patterns of trains of clicks (trills) and click rates are unique to each species. While the mechanism of sound production is highly conserved, the rates at which these clicks are produced and thus the rate at which laryngeal muscles contract vary considerably among species, from two clicks per second in X. borealis (Yager 1992) to 70 in X. laevis (Kelley 2002). This variation in muscle contraction rates provides an opportunity to examine how MyHC isoform expression changes under selection for the trill rates of species-specific calls.…”
Section: Introductionmentioning
confidence: 99%
“…Sound production does not require airflow; the contraction of a single laryngeal muscle group causes the snapping apart of paired discs and a resulting click (Yager, 1992), the basic unit of all calls. The simplified mechanism of Xenopus call production makes it an attractive model for addressing how vocalizations are produced and also offers the opportunity to investigate how breathing and calling can be regulated in a temporally distinct manner.…”
Section: Introductionmentioning
confidence: 99%